An epidemiological study on acute febrile illness: its risk factors and preventive aspects in Unani medicine - Zahoor, Syed Abdul; Hussain, Mohammed Maqbool; Ifath, Juveriya; Sultana, Kouser; Tabassum, Sumaiya; Hafsa; Zainab, Femina (International Journal Of Community Medicine And Public Health, 2025)
Background: Acute febrile illness (AFI) presents a major health problem marked by raised body temperature and related symptoms, which Unani medicine understands through its special humoral paradigm. Within the conventional Unani medical system, this study investigates the basic ideas, risk factors, and preventative strategies for acute fever. Methods: We conducted a prospective observational study involving 200 participants diagnosed with AFI in outpatient department attendees of the department of community medicine, Government Nizamia Tibbi College and Hospital. from July 2024 to December 2024. Data Analysis was by SPSS. Results: The study identified several key risk factors for AFI, including e.g., poor sanitation, lack of vaccination, environmental factors. Additionally, Unani preventive strategies, such as the use of specific herbal remedies, dietary modifications, and lifestyle changes, demonstrated efficacy in reducing the incidence of AFI. Participants who adhered to Unani preventive measures exhibited a reduction in AFI symptoms. Conclusions: The findings underscore the importance of integrating traditional Unani practices with modern public health initiatives to effectively address AFI. By leveraging the strengths of both approaches. Further research is recommended to explore the mechanisms of action of Unani interventions and their potential for broader application in public health.